Early childhood nutrition and academic achievement: a longitudinal analysis - Glewwe, Paul; Jacoby, Hanan; King, Elizabeth M. (International Food Policy Research Institute, 1999)
Early childhood nutrition is thought to be an important input into subsequent academic achievement. This paper investigates the nutrition-learning nexus using a unique longitudinal data set, which follows a large sample of Philippine children from birth until the end of their primary education. We find that malnourished children perform more poorly in school, even after correcting for the effects of unobserved heterogeneity both across and within households. Part of the advantage that well-nourished children enjoy arises from the fact that they enter school earlier and thus have more time to learn. The rest of their advantage appears to stem from greater learning productivity per year of schooling rather than from greater learning effort in the form of homework time, school attendance, and so forth. Despite these findings, our analysis suggests that the relationship between nutrition and learning is not likely to be of overriding importance either for nutrition policy or in accounting for economic growth.